Comparison of immunofluorescence and desmoglein enzyme-linked immunosorbent assay in the diagnosis of pemphigus: A Prospective, Cross-sectional Study in a Tertiary Care Hospital - Deepthi Ravi; S Smitha Prabhu; Raghavendra Rao; C Balachandran; Indira Bairy (Wolters Kluwer Medknow Publications, 2017)
Background: Pemphigus is an acquired immunobullous disorder in which antibodies are directed against epidermal cadherins. Despite the commercial availability and less cost of enzyme-linked immunosorbent assays (ELISAs) to detect antidesmoglein 1 (Dsg1) and anti-Dsg3, immunofluorescence is still widely used for confirmation of diagnosis. Aims: (1) To compare the usefulness of indirect immunofluorescence (IIF) and ELISA tests in the diagnosis of pemphigus. (2) To find the clinical correlation between the tests and severity of the disease. Materials and Methods: Sixty-one patients (27 women and 34 men, age distribution from 20 to 75) were clinically diagnosed as pemphigus (pemphigus foliaceus - 11, pemphigus vulgaris - 50) and were recruited for the study. IIF and Dsg ELISA were performed and the findings were compared with each other and with the pemphigus area activity score. Data were entered in SPSS and were analyzed using Kruskal-Wallis test. Results: There was a moderate positive correlation between the cutaneous score and Dsg1 titer, and mucosal score and Dsg3 titer. The titer of IIF showed statistically significant positive correlation with the cutaneous score but not the mucosal score. Dsg ELISA showed higher sensitivity (90.2%) than IIF (75.4%) in the diagnosis of pemphigus. Conclusions: Dsg ELISA is a more sensitive method than IIF and shows more correlation with the disease severity.